Intersectional perspectives on gendered adaptation and social hierarchies in agricultural communities of the Indian Himalaya - Akshita Choudhary; Michelle Bonatti; Stefan Sieber; Deepali Tewari Pandey; P. K. Joshi (Discover Sustainability)
Abstract The Indian Himalayan states are among the most vulnerable regions to climate change experiencing declines in agricultural production, food security, and livelihood options. However, the importance of socio-economic factors on adaptation within agricultural communities remains largely underexplored. This study examines the effect of gender, social groups and other socio-economic factors influencing adaptation choices using multivariate probit modelling. Using intersectional perspective, the study explores how diverse socio-economic factors interact and affect the adoption of adaptation strategies in response to climate change impacts. Hierarchical clustering was used to create four social groups based on various socio-economic characteristics, such as income, reservation category (based on caste), family size, education, and income level. Using a stratified random sampling technique, primary data was gathered from 298 sample households in the district Almora of Uttarakhand state in the Indian Himalaya. The findings reveal disparities such as female-headed households rely more on social and ecosystem-based strategies to maintain productivity and ensure food security whereas male-headed households are more predominant in technological and institutional strategies. Regardless, lower social groups of male and female-headed households rely more heavily on ecosystem-based approaches to address climate risks, due to their limited access to the technologies and financial resources that are more prevalent in higher social groups. The results highlight how gender and other socio-economic factors interacts and influence the choice of different strategies. The study claims that an intersectional approach can go beyond binary male and female categories and further investigates at the inter-categorical and intra-categorical level of gender intersectionality. The study contributes to effective adaptation planning and polices by understanding how various socio-economic factors intersects to shape differential vulnerabilities and adaptation strategies.